Association between chronic obstructive pulmonary disease and periodontitis: The common role of innate immune cells?. (October 2022) - Ouyang, Yuanting; Liu, Jiaohong; Wen, Siyi; Xu, Yixin; Zhang, Zhiyi; Pi, Yixing; Chen, Ding; Su, Zhikang; Liang, Zitian; Wang, Yan; Guo, Lvhua
Highlights: Summarized the relationship between chronic obstructive pulmonary disease (COPD) and periodontitis from recent articles, clinical studies, epidemiological investigations, prospective studies, etc. Excessive neutrophil extracellular traps (NETs) formation occur during dysregulation of inflammation in patients with COPD and periodontitis and might be a potential biomarker of disease severity. Elaborated multiple immune mechanisms of periodontitis and COPD. Provide new ideas for the comorbid treatment of subsequent COPD and periodontitis. Abstract: Innate immune cells are of broad interest in a variety of diseases. These cells include neutrophils, macrophages, dendritic cells and mast cells, etc. Innate immune cells are often mentioned in inflammatory diseases as the first line of defense against pathogens' invasion. As chronic obstructive pulmonary disease and periodontitis are inflammatory diseases, innate immune cells play an important role in the development of both diseases. COPD and periodontitis are common epidemic diseases with a very high prevalence, thus affecting a large number of people and also reducing the quality of life of patients. In addition, epidemiological studies suggested a link between the two, creating a co-morbid burden, but the mechanism of the link is yet to be explained. This article discusses the possible mechanism of the link between the two diseases in terms of innate immune cells and discusses possible future targeted therapies that could alleviate the burden on patients.